Genetic diversity among ethiopian coffee (Coffea Arabica L.) collections available in indian gene bank using sequence related amplified polymorphism markers - Mishra, Manoj Kumar; Nishani, Sandhyarani; Gowda, Madhura; Padmajyothi, Dandamudi; Suresh, Narayana; Sreenath, Hosahalli; Raghuramulu, Y. (Plant Breeding and Seed Science, 2014)
The South-Western highlands of Ethiopia are considered to be the centre of origin and diversity of the arabica coffee, Coffea arabica. More than 80 accessions of arabica coffee collected from Ethiopia are avail-able in Indian gene bank. However, the genetic diversity of these accessions is not studied in detail. In the present study, genetic diversity analysis of 48 accessions collected from eight provinces of Ethiopia was car-ried out using Sequence-related amplified Polymorphism (SRAP) marker. Among the thirty two SRAP primer combinations tested, 14 primer pairs were polymorphic and generated 203 distinct fragments. The number of fragments ranged from 7 to 21 with a mean of 14.5 fragments per primer combination. Of the total 203 ampli-fied fragments, 182 (89.65%) were polymorphic and the percent of polymorphism ranged from 53.84% to a maximum of 100% using different primers. The average resolving power (Rp) and average polymorphism information content (PIC) of the 14 SRAP primer combinations was 14.31 and 0.648 respectively. A total of 13 rare alleles were obtained from SRAP assays, of which six rare alleles were obtained from the accessions collected from Shoa province. The UPGMA clustering algorithm from SRAP analysis grouped the 48 coffee accessions into two major clusters. The accessions collected from particular province clustered together which could be attributed to the substantial gene flow between adjacent population and the influence of geographical origin on genetic diver-sity. The study demonstrated the existence of substantial genetic variation in Ethiopian germplasm which could be utilized in coffee germplasm conservation and improvement program.